Food bodies in Cissus verticillata (Vitaceae): ontogenesis, structure and functional aspects - Sousa Paiva, Elder Antonio; Buono, Rafael Andrade; Lombardi, Julio Antonio [UNESP] (Oxford University Press, 2009)
The distinction between pearl bodies (or pearl glands) and food bodies (FBs) is not clear; neither is our understanding of what these structures really represent. The present work examined the ontogenesis, structure, ultrastructure and histochemical aspects of the protuberances in Cissus verticillata, which have been described since the beginning of the 19th century as pearl glands or pearl bodies, in order to establish a relationship between their structure and function.Segments of stems and leaves in different stages of development were collected and fixed for study under light microscopy as well as electron transmission and scanning microscopy. Samples of FBs were subjected to chemical analysis using thin-layer chromatography.The FBs in C. verticillata are globose and attached to the plant by a short peduncle. These structures are present along the entire stem during primary growth, and on the inflorescence axis and the abaxial face of the leaves. The FBs were observed to be of mixed origin, with the participation of both the epidermis and the underlying parenchymatic cells. The epidermis is uniseriate with a thin cuticle, and the cells have dense cytoplasm and a large nucleus. The internal parenchymatic cells have thin walls; in the young structures these cells have dense cytoplasm with a predominance of mitochondria and plastids. In the mature FBs, the parenchymatic cells accumulate oils and soluble sugars; dictyosomes and rough endoplasmic reticulum predominate in the cytoplasm; the vacuoles are ample. Removal of the FBs appears to stimulate the formation of new ones, at the same place.The vegetative vigour of the plant seems to influence the number of FBs produced, with more vigorous branches having greater densities of FBs. The results allow the conclusion that the structures traditionally designated pearl glands or pearl bodies in C. verticillata constitute FBs that can recruit large numbers of ants.